General Analysis of Directional Ocean Wave Data from Heave Pitch Roll Buoys - Stephen F. Barstow; Harald E. Krogstad (Modeling, Identification and Control, 1984)
Directional ocean wave data is usually analysed using the so-called linear model of the sea surface, but experience has shown that the results may deviate substantially from the predictions of the theory, in particular in the high frequency range. A general theory is presented here which includes the linear model as a special case. Properties of commonly used parameters under the influence of currents and non-linearities are easily explained within the general theory. Some results from the NORWAVE heave/pitch/roll data buoy operated offshore Norway are also presented.